2016
DOI: 10.1038/tp.2016.103
|View full text |Cite
|
Sign up to set email alerts
|

Crucial roles of the CHRNB3–CHRNA6 gene cluster on chromosome 8 in nicotine dependence: update and subjects for future research

Abstract: Cigarette smoking is a leading cause of preventable death throughout the world. Nicotine, the primary addictive compound in tobacco, plays a vital role in the initiation and maintenance of its use. Nicotine exerts its pharmacological roles through nicotinic acetylcholine receptors (nAChRs), which are ligand-gated ion channels consisting of five membrane-spanning subunits. Besides the CHRNA4, CHRNB2 and CHRNA5/A3/B4 cluster on chromosome 15, which has been investigated intensively, recent evidence from both gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 112 publications
0
22
0
Order By: Relevance
“…Constitutive expression of the 6Ld mutation conferred exaggerated behavioral responses to nicotine, high liability to addiction, increased DA release to a nicotine challenge, and induction of functional plasticity phenomena, such an abnormal increase of GluR1 AMPA receptor subunit expression in the VTA DA neurons ( Drenan et al, 2010 ; Berry et al, 2015 ). Genetic association for the risk of developing nicotine dependence was recently confirmed for one polymorphism within the CHRNB3–CHRNA6 gene cluster ( Wen et al, 2016 ). Hypothetically, this liability may become particularly relevant in case an individual carrying some nAChR risk polymorphisms is exposed to nicotine during the last gestational period, as in the case of smoking women during pregnancy.…”
Section: Discussionmentioning
confidence: 94%
“…Constitutive expression of the 6Ld mutation conferred exaggerated behavioral responses to nicotine, high liability to addiction, increased DA release to a nicotine challenge, and induction of functional plasticity phenomena, such an abnormal increase of GluR1 AMPA receptor subunit expression in the VTA DA neurons ( Drenan et al, 2010 ; Berry et al, 2015 ). Genetic association for the risk of developing nicotine dependence was recently confirmed for one polymorphism within the CHRNB3–CHRNA6 gene cluster ( Wen et al, 2016 ). Hypothetically, this liability may become particularly relevant in case an individual carrying some nAChR risk polymorphisms is exposed to nicotine during the last gestational period, as in the case of smoking women during pregnancy.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, individuals with genetic variations that result in diminished function of these nAChR subunits may experience less nicotine withdrawal that, in turn, facilitates smoking cessation (Salas et al, 2009;Stoker et al, 2015). Although human studies, in general, do not distinguish affective vs. physical aspects of nicotine withdrawal/dependence, many nAChR subunits (e.g., a2, a3, a5, a6, b3, b4) have been detected in human GWAS for nicotine dependence (Greenbaum & Lerer, 2009;Wen et al, 2016).…”
Section: Animal Genetic Studiesmentioning
confidence: 99%
“…A recent survey by counted a total of 287 human genetics studies on nicotine dependence, including 242 candidate gene association, 22 genome-wide linkage, 18 GWAS, and five targeted sequencing studies. We refer readers to existing reviews for detailed findings (Greenbaum & Lerer, 2009;Wang & Li, 2009;Lassi et al, 2016;Wen et al, 2016). In brief, several neurotransmitter systems, such as the acetylcholinergic, dopaminergic, GABAergic, and glutamatergic systems, have been implicated.…”
Section: Human Genetic Studiesmentioning
confidence: 99%
“…There is strong evidence from adoption, family, and twin studies that both genetic and environmental factors contribute to risk for smoking behaviors, with heritability estimates for nicotine dependence, ever becoming a regular smoker, and smoking quantity ranging between 33% and 71% [4][5][6][7][8] . Recently, genome-wide association studies (GWAS) have identified common variants associated with smoking behaviors 1,[9][10][11][12][13] . In particular, the nicotinic acetylcholine receptor subunit genes CHRNA5-CHRNA3-CHRNB4 on chromosome 15 have been identified in well-powered GWAS of smoking behaviors 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the nicotinic acetylcholine receptor subunit genes CHRNA5-CHRNA3-CHRNB4 on chromosome 15 have been identified in well-powered GWAS of smoking behaviors 14,15 . Within CHRNA5, which codes for the α 5 receptor subunit, the nonsynonymous G/A single nucleotide polymorphism (SNP) rs16969968 has been replicated through both large-scale GWAS 1,[9][10][11][12][13]16 and functional assays [17][18][19][20] to influence smoking quantity, as measured by the number of cigarettes smoked per day, and nicotine dependence. The rs16969968-A risk allele has the largest estimated allelic effect on smoking quantity known to date 13 .…”
Section: Introductionmentioning
confidence: 99%